Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Literasi Sains Peserta Didik Kelas V SDN Karangtanjung Pada Materi Cahaya dan Sifatnya - Ningrum, Lintang Ayu; Lestari, Wahyu Maulida (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine the effect of the guided inquiry learning model on the science literacy skills of fifth-grade students at SDN Karangtanjung in the topic of light and its properties. The research employed a quantitative approach using a one-group pretest-posttest design. The instrument consisted of 20 multiple-choice items, of which 18 were declared valid after validation. A reliability test showed a Cronbach’s Alpha value of 0.794. The Shapiro-Wilk test confirmed that the data were normally distributed, and a paired sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between the pretest and posttest. The average score increased from 53.73 to 85.27. The highest improvement occurred in the indicator of interpreting data and scientific evidence (84.69%), followed by designing and evaluating scientific inquiry (68.42%), and explaining scientific phenomena (28.12%). These findings suggest that the guided inquiry model is effective in enhancing science literacy through active, exploratory, and experience-based learning.